2018
DOI: 10.1016/j.topol.2018.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Crossing numbers of random two-bridge knots

Abstract: In a previous work, the first and third authors studied a random knot model for all two-bridge knots using billiard table diagrams. Here we present a closed formula for the distribution of the crossing numbers of such random knots. We also show that the probability of any given knot appearing in this model decays to zero at an exponential rate as the length of the billiard table goes to infinity. This confirms a conjecture from the previous work. 1 knots are parametrized by the already-closed curve (cos(at + φ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Both [CK15] and [CEZK18] discuss moves on billiard table diagrams that are similar to Reidemeister moves: the internal reduction move that deletes a run + + + or − − − of three in a row and the external reduction move that deletes + + − or − − + only from the start of the word or − + + or + − − only from the end of the word.…”
Section: Alternating Diagrams Of 2-bridge Knotsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both [CK15] and [CEZK18] discuss moves on billiard table diagrams that are similar to Reidemeister moves: the internal reduction move that deletes a run + + + or − − − of three in a row and the external reduction move that deletes + + − or − − + only from the start of the word or − + + or + − − only from the end of the word.…”
Section: Alternating Diagrams Of 2-bridge Knotsmentioning
confidence: 99%
“…The author with Krishnan [CK15] and with Even-Zohar and Krishnan [CEZK18] developed a random model for these a = 3 Chebyshev diagrams by taking a random string of {+, −} n , where n = b − 1 is the number of crossings of the diagram and where + and − correspond to the slope of the overstrand in the crossing: and , respectively. Because a = 3, the only knots appearing in this model are 2-bridge knots and the unknot.…”
Section: Introductionmentioning
confidence: 99%
“…Baader, Kjuchukova, Lewark, Misev, and Ray [BKLMR19] previously showed that if c is sufficiently large, then c 4 ≤ g c . The proof of Theorem 1.1 uses the Chebyshev billiard table model for knot diagrams of Koseleff and Pecker [KP11b,KP11a] as presented by Cohen and Krishnan [CK15] and with Even-Zohar [CEZK18]. This model yields an explicit enumeration of the elements of K c as well as an alternating diagram in the format of Figure 2 for each element of K c .…”
Section: Introductionmentioning
confidence: 99%
“…A given 2-bridge knot has infinitely many descriptions as strings of various lengths in the symbols {+, −}. Cohen, Krishnan, and Evan-Zohar's work [CK15,CEZK18] lets us describe 2-bridge knots in this manner but with more control on the number of strings representing a given 2-bridge knot.…”
Section: Introductionmentioning
confidence: 99%